b - Forsberg, Randall; Crawford, Neta; Evangelista, Matthew, 1958-; Project Muse. (Cornell University Press, 2019)
"This book explores the conditions under which the institution of war could be brought to an end. It draws on an extensive program of research into the phenomenon of socially sanctioned violence and focuses on the role of moral beliefs. This book explores social change and the goal of eradicating mass violence"--
The idea of a theory of peace -- Conditions for the abolition of war -- The roles of innate impulses and learned moral beliefs in individual and group violence -- Socially sanctioned group violence : features, examples, and sources -- Ritual cannibalism : a case study of socially sanctioned group violence -- Sanctioned violence, morality, and cultural evolution -- Appendix : the debate on the existence of cannibalism.
"An edited version of the thesis by the same name submitted by Randall Caroline Watson Forsberg in May 1997 to the Department of Political Science at the Massachusetts Institute of Technology, where she was studying for her Ph. D."--Editors' note.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Violence -- Moral and ethical aspects; War -- Moral and ethical aspects; Peace -- Moral and ethical aspects; Electronic books